Analisis Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan Dan Kepemilikan Manajerial terhadap Manajemen Laba pada Perusahaan Properti and Real Estate yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2017-2021 - Nur Azizah; Sri Sudarsi (J-MAS (Jurnal Manajemen dan Sains), 2023)
The study examines thei effecti ofi profitability, leverage, firmi sizei, andi manageriali ownershipi oni earningsi managementi. The population in thisi study were all property and real estate companies for the 2017-2021 period, totaling 79 companies. By using a purposive sampling technique, a total sample of 23 companies was obtained that met the sample criteria for a 5 year period. The analytical tool was multiple regression where the classical assumption test was carried out with the SPSS 26 program and Microsoft Excel.